Tinjauan Desain Furniture dan Suasana Pada Kafé Wongkis 76 - Lestari, Siti Indah; Salma, Afifah (Waca Cipta Ruang, 2023)
The cafe is a place that is very popular with many people, from young people to old people. Cafe is usually visited as a place to eat and drink with a relaxed atmosphere. But along with the development of the times more and more various types of cafes are present, this place is visited not only to eat and drink in a relaxed atmosphere but some people come to the cafe for a business job, family gatherings, and millennials who usually just want to get an additional collection of aesthetic photo spots. In this study, I conducted a review of the wongkis 76 cafe located on Jl. Telaga Sari, Tanjung Morawa District, Deli Serdang Regency, North Sumatra. The method I use in this research is a descriptive research method with a qualitative method approach. The data was collected from a field observation by conducting a survey directly to the location that I reviewed, namely wongkis 76 Café. From the results of the survey, I found several problems that exist in Wongk is 76 cafe, these problems include the narrow cafe space in several spaces for walking and one of them is on the stairs from the 1st floor to the 2nd floor. Some of the furniture the chairs in this cafe are not ergonomic and the size is not in accordance with the anthropometry of the human body, where the ergonomic shape of a chair greatly affects the comfort of the visitors. The purpose of this research I did to find out the problems that exist in wongkis 76 Cafe and find solutions to these problems.